Giant choledochal cyst in infant: A rare case report - Ram Jeewan Singh; Md Mokarram Ali; Rashi Rashi; Amit Kumar; Shreyas Dudhani; Amit Kumar Sinha (Wolters Kluwer Medknow Publications, 2023)
The cystic dilatation of the common bile duct (CBD) is a rare pathology in an infant. It is the second-most common surgical cause of cholestatic jaundice in infants after biliary atresia. A 4-month-old female child was admitted to our department with complaints of abdominal distension. The physical examination revealed the presence of a huge palpable mass involving the right hypochondrium up to the right iliac fossa and umbilical region. Ultrasound abdomen revealed a large intra-abdominal cyst but unable to comment on the organ of origin of the cyst due to its huge size. Multidetector computed tomography of the abdomen was suggestive of possible origin of the cyst from CBD extending from porta hepatis to pelvis. At laparotomy, there was a huge choledochal cyst extending from porta hepatis to pelvis. The choledochal cyst was excised, followed by Roux-en-Y hepaticojejunostomy.